The Effect of Procedural Justice on Organizational Commitment in the Malaysian Context: Do Men and Women Differ? - Aizzat Mohd. Nasurdin; Zainal Ariffin Ahmad (Asian Academy of Management Journal, 2001)
The purpose of this paper is to determine the influence of procedural justice on organizational commitment and wether gender differences play a role in moderating the above-mentioned relationship among Malaysian employees. Based on the social exchange framework (Blau, 1964), the norm of reciprocity (Gouldner, 1960), and the "group-value" model (Lind & Tyler, 1988) a study was conducted among hotel workers in Malaysia. Analyses of 161 responses reveal that procedural justice does have a significant effect on organizational commitment. While gender does not moderate the effect of procedural justice on employees' commitment , the findings may suggest a trend toward similiraty in beliefs, values, and attitudes towards work among male and females in the Malaysian workforce. Implications for managerial practice and future research are discussed.